2007
DOI: 10.3354/meps329099
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the distribution of the scyphomedusa Chrysaora quinquecirrha in Chesapeake Bay

Abstract: Jellyfish blooms are important events controlling plankton dynamics in coastal waters worldwide, yet factors that influence bloom development are not well understood. We used the scyphomedusa Chrysaora quinquecirrha as a model to examine physical factors that control jellyfish populations and to develop an ecological forecasting system. Over 700 in situ observations collected from Chesapeake Bay and its tributaries during 1987-2000 were used to develop habitat models that predict the probability of occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 41 publications
1
56
0
1
Order By: Relevance
“…The decline in M. leidyi blooms in the York River estuary appears to be due primarily to predation by C. quinquecirrha scyphomedusae, and not to bottom-up food limitation of M. leidyi. Chrysaora medusae appeared in surface waters early to mid-summer (June-July) at water temperatures > 25°C and salinities ranging from 16 to 20 psu (Decker et al 2007) (Fig. 6).…”
Section: Factors Influencing Timing and Magnitude Of Mnemiopsis Leidymentioning
confidence: 99%
“…The decline in M. leidyi blooms in the York River estuary appears to be due primarily to predation by C. quinquecirrha scyphomedusae, and not to bottom-up food limitation of M. leidyi. Chrysaora medusae appeared in surface waters early to mid-summer (June-July) at water temperatures > 25°C and salinities ranging from 16 to 20 psu (Decker et al 2007) (Fig. 6).…”
Section: Factors Influencing Timing and Magnitude Of Mnemiopsis Leidymentioning
confidence: 99%
“…Jung & Houde (2004) found that larval mortality rates in the mainstem of the Chesapeake Bay were lower in years with high salinity (dry years), potentially because of the effects of salinity on predator abundance and spatial distribution (Purcell & Decker 2005). Year types (wet/dry) affect the spatial distribution of sea nettles (Decker et al 2007), as well as the timing of peak sea nettle abundance (Breitburg & Fulford 2006). The potential effect of year types on ctenophores is less clear, as they do not appear to be affected by temperature and salinity, but may be affected by food availability and sea nettle predation (Purcell & Decker 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The reason we chose to do the likelihood test on wind direction and tide as categorical variables, in addition to the more dynamical multivariate approach described below, was to attempt to have a easy to use decision tool for lifeguards patrolling what is a popular tourist beach. Logistic regression analysis has previously been used (Decker et al, 2007) to relate jellyfish presence/ absence data to environmental variables. We used a similar approach using the LOGIT module in SYSTAT (Systat Software Inc., San Jose, USA) to determine which predictor variable contributed the best fit to the regression, and which combination of environmental variables best described the relationship between the occurrence of jellyfish strandings and the potential environmental predictor variables of tide range, model current direction and speed, wind speed and wind direction at Broome.…”
Section: Predictors Of Beach Stranding Eventsmentioning
confidence: 99%